(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Muscle relaxant can be effective in pain management. This review article aims to check to the effectiveness of muscle relaxant for reducing pain due to muscle contraction. Muscle relaxants are drugs that assistance to relieve muscular spasm, which are spontaneous muscle contraction produced by the spine-related condition like stroke, fibromyalgia, or low back strain. Muscle spasms can be unbearably painful and damage movement. Skeletal muscle relaxants are a varied range of structurally unrelated drugs with varying pharmacologic and safety profiles, while being grouped under a same pharmacological class. Spasticity and local musculoskeletal spasms are two disorders that are routinely treated with skeletal muscle relaxants.